The Beauty of Geology: Art of Geology Mapping in China Over a Century - Li, Chenyang; Jia, Liqiong; Wu, Xuan (Springer Nature Singapore : Imprint: Springer, 2019)
This open access book contains a collection of rare geologic maps and figures made by Chinese geologists in the last century. Preserved in National Geological Archives of China, these artworks demonstrate the development and innovation of geological mapping technology in China in the past 100 years. The collections are highly scientific and artistic, with most of the hand-drawn maps featured with traditional Chinese painting techniques, while the newer ones being more accurate and embedded with more scientific information with the aid of computer technics.